Fueling Our Future : An Introduction to Sustainable Energy - Evans, R (Cambridge University Press, 2013)
This book takes a systems approach to energy use, so that the complete consequences of choosing a particular energy source, or energy conversion system, can be seen. The concept of the complete energy conversion chain, which is a simple but powerful tool for analyzing any energy consuming process, is introduced to link primary energy resources through to the ultimate end-use. Looking at the complete consequences of any proposed energy technology in this way enables the reader to see why some proposed solutions are more sustainable than others, and how the link between energy consumption and greenhouse gas emissions can be broken. This simple systems approach is essential to provide a global understanding of how we can begin the transition to a truly clean and sustainable energy future.